Research on the Hierarchical Interactive Teaching of Middle School Chemistry Based on the Theory of "Mind Map" - Cheng, Xianghua; Xu, Suyi; Cao, Zhongyan; Xu, Ying (Advances in Social Sciences Research Journal, 2022)
The hierarchical interactive teaching model under the guidance of mind map theory advocates problem stratification, intelligence stratification, interactive teaching, cooperative learning, which comprehensively cultivates students' divergent thinking and inquiry ability on the basis of respecting students' differentiated development, so as to implement the core literacy of chemistry. It is a good teaching mode of teaching students in accordance with their aptitude. Based on the actual situation of middle school chemistry teaching in China, this paper analyzes the problems existing in the current teaching, discusses the relationship between this model and China′s education policy, as well as the specific methods and strategies of application in middle school teaching design. Taking "The Properties of Chlorine" as an example, the specific teaching design is carried out to explore the specific path of integrating hierarchical interactive teaching mode into chemistry teaching in China, in order to promote the application of this mode in high school chemistry teaching.